The Construction of Maputo-KaTembe Bridge and The Dynamics of Land Occupation in The Municipal District of KaTembe – Mozambique - Chicombo, Tomé Francisco (Sociedade & Natureza, 2022)
The present study analyses the influence of the Maputo-KaTembe bridge in changing the dynamics of land occupation in the municipal district of KaTembe. The bridge was inaugurated on November 10, 2018, and from there came the expectation of a new development scenario in the district and new dynamics of urban growth. Spatial patterns and the intensification of urbanization were shown using cartography tools. The study aimed to understand the dynamics before and after the construction of the bridge, in order to show new trends with the start of operation of the bridge, which was already expected. Images were visually interpreted in Google Earth at different times before and after the construction of the bridge, verifying the patterns of growth of the occupied area and validating of the manual classification of the images in the Google Earth platform. The Results and the map produced showed an intensification of land occupation in the district from the start of the operation of the bridge. Despite the expansion of the urban fabric, measures must be taken to prevent problems in the future, especially for the environmental problems (floods, pressure on natural resources, coastal erosion, etc.) and social problems (socio-spatial segregation, mobility). These measures include planning and managing the process of land use and occupation.